MODERASI BERAGAMA PERSFEKTIF KH. ABDURRAHMAN WAHID - Alifatudz dzakiyyah; Ali Ahmad Yenuri (Journal Multicultural of Islamic Education, 2024)
One of the figures who is intent and concerned about expressing moderate Islam is KH. Abdurrahman Wahid. His thoughts and ideas deserve to be interpreted in moderate Islam. Abdurrahman Wahid is a Muslim intellectual figure who comes from an Islamic boarding school environment. One of his ideas is that washatiyah Islam must act moderately and apply justice in national and state abstrack: life as a mandatory condition in efforts to maintain peace in Indonesia in particular and world peace in general. The concept of Washatiyah Islam is important to apply in plural Indonesia as well as to stem the Islamic caliphate movement. He is called the father of national pluralism. This research concludes that Gus Dur's pluralism perspective on religious moderation is that religious moderation is a conception that can build a tolerant and harmonious attitude in order to strengthen national unity and integrity.keyword: Abdurrahman Wahid, religious moderation, pluralism